Dynamic Blood Concentrations of Aβ1–40 and Aβ1–42 in Alzheimer’s Disease - Yang, Yuan-Han; Huang, Ling-Chun; Hsieh, Sun-Wung; Huang, Li-Ju (Frontiers in Cell and Developmental Biology, 2020)
Amyloid-beta (Aβ) is produced by the cleavage of amyloid precursor proteins into a monomeric form with peptides of different lengths such as Aβ1-40 or Aβ1-42, which is then transformed into oligomeric and fibril forms and is considered to be one of the hallmarks of Alzheimer’s disease (AD). The plasma concentrations of Aβ1-40 and Aβ1-42 are unstable after blood samples have been obtained. In order to examine the dynamic changes of plasma Aβ1-42 and Aβ1-40 in blood samples, we used fresh blood samples from 32 clinically diagnosed AD patients. Each sample was subdivided into eight sub-samples, and levels of Aβ1-40 and Aβ1-42 were measured at 0 (baseline), 0.5, 1, 2, 3, 5, 8 and 24 hours, respectively. All samples were incubated at 37ºC before being measuring. The results showed that compared to baseline, 87.5% and 62.5% of the patients had higher plasma levels of Aβ1-42 and Aβ1-40 at 24 hours, respectively. The patients with an increased amyloid level did not have a significantly different apo-lipoprotein E4 allele (APOE4) gene status for either Aβ1-40 (p=0.422) or Aβ1-42 (p=1.000). However, for plasma Aβ1-42, the APOE4 carriers had a significantly lower level than the non-carriers at baseline (31.2±6.5 (mean± SD) ng/ml vs 50.4±47.7 ng/ml, p=0.031) and 0.5 hours (37.5±7.6 ng/ml vs 51.9±30.8 ng/ml, p=0.043). There were no significant differences between the APOE4 carriers and non-carriers in plasma Aβ1-42 concentration at 1, 2, 3, 5, 8 and 24 hours (p=0.112, p=0.086, p=0.112, p=0.263, p=0.170 and p=0.621, respectively). The Aβ1-40 level was related to disease severity as assessed using the clinical dementia rating (CDR) scale. Patients with advanced stages of dementia (CDR=1 and CDR=2) had a significantly higher Aβ1-40 level compared to those with very mild stage dementia (CDR=0.5) at all time points (p<0.05) except for 24 hours (p=0.059). Our findings illustrate the effects of APOE4 status on dynamic changes in plasma Aβ1-40 and Aβ1-42 levels, and significant associations between Aβ1-40 level and disease severity. Further studies are needed to investigate the exact mechanisms of how APOE4 affects the dynamic changes in plasma Aβ1-40 and Aβ1-42, and the association between Aβ1-40 and advanced dementia.